2004
DOI: 10.1007/s00422-004-0476-4
|View full text |Cite
|
Sign up to set email alerts
|

Saturation in excitatory synapses of hippocampus investigated by computer simulations

Abstract: The standard view of the synaptic function in excitatory synapses has been deeply questioned by recent experimental data on hippocampal glutamate synapses both for possible receptor nonsaturation and for larger and non-Gaussian peak amplitude fluctuations. Our previous investigations of the mechanisms involved in the variability of the response of hippocampal glutamatergic synapses, carried out by computer simulation of simple Brownian models of glutamate diffusion, furnished initial evidence about their presy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…This observation definitely makes obsolete the widespread conception of a simple prolongation of the extracellular space. Consequently, neurotransmitters might not be able to diffuse as freely as was previously thought, and computer simulation-based models will have to incorporate these data (35)(36)(37). Similarly, postsynaptic neurotransmitter receptor diffusion, which is implied in synaptic plasticity (38), might be affected by the organized complexes.…”
Section: Discussionmentioning
confidence: 99%
“…This observation definitely makes obsolete the widespread conception of a simple prolongation of the extracellular space. Consequently, neurotransmitters might not be able to diffuse as freely as was previously thought, and computer simulation-based models will have to incorporate these data (35)(36)(37). Similarly, postsynaptic neurotransmitter receptor diffusion, which is implied in synaptic plasticity (38), might be affected by the organized complexes.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the experiments carried out to analyze the binding process imposed the stationarity of the concentration of neurotransmitters within the synaptic cleft and a long period, of the order of milliseconds, of exposition of receptors to Glutamate (Clements et al 1992;Jonas et al 1993). Conversely, in real conditions in which the neurotransmitters are released by a docked vesicle, the flow of neurotransmitters within the cleft is far from stationarity [we can see this also from Figure 6 in Ventriglia and Di Maio (2013b)] and the diffusion process of GLUT within the synaptic cleft is much faster than supposed (100s against 1,000s of microseconds) (see Forti et al 1997;Ventriglia 2004Ventriglia , 2011Ventriglia and Di Maio 2013a). …”
Section: Binding Probabilitymentioning
confidence: 65%
“…The model is simulated on a parallel computer by using an ultra-fast time scale (simulation step = 40 fs). The early results of the simulation demonstrated that intrinsic random variations in basic pre-synaptic elements of the synapse can reproduce some aspects of the observed stochastic variability of the peak amplitude of miniature excitatory post synaptic current (mEPSC) Di Maio 2000, 2003;Ventriglia 2004). Some recent simulations investigated the effects of the inclusion into the model of new data on structural elements such as the presence of filaments extending across the synaptic cleft (Araç et al 2007;Zuber et al 2005; Ventriglia 2011 and references therein), the (increased) size and the (lower) number of post-synaptic receptors and analyzed the consequences of the increase of the number of AMPA receptors-linked to trafficking-on the synaptic response (Ventriglia and Di Maio 2013a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The plasma membrane and the recording electrode were simulated as two parallel plates. The simulation of the transmitter (free) diffusion in the vesicle (but also in the pore and the space between the plasma membrane and the electrode) followed methods described previously (Glavinović 1999;Ventriglia 2004). Note that the transmitter molecules bound to the gel are not able to diffuse.…”
Section: Theorymentioning
confidence: 99%